Genetics and Hemostatic Potential in Persons with Mild to Moderate Hemophilia A with a Discrepancy between One-Stage and Chromogenic FVIII Assays - Strålfors, Annelie; Mikovic, Danijela; Schmidt, David; Onelöv, Liselotte; Soutari, Nida Mahmoud Hourani; Berndtson, Maria; Chaireti, Roza; Holmström, Margareta; Antovic, Jovan P.; Bruzelius, Maria (Thrombosis and Haemostasis, 2020)
Background Factor VIII (FVIII) activity (FVIII:C) can be measured by different methods including one-stage clotting assays (OSAs) and chromogenic assays (CSAs). Discrepancy between FVIII:C assays is known and associated with genetic variations causing mild and moderate hemophilia A (HA). We aimed to study the discrepancy phenomenon and to identify associated genetic alterations. Further, we investigated if hemostatic global assays could discriminate the group with discrepant FVIII:C from them.Methods The study contained plasma samples from 45 patients with HA (PwHA) from Hemophilia Centers in Stockholm, Sweden, and Belgrade, Serbia. We measured FVIII:C with OSA and CSA, sequenced the F8 gene, and performed two global hemostatic assays; endogenous thrombin potential and overall hemostatic potential.Results Nineteen of 45 PwHA had a more than twofold higher FVIII:C using OSA compared to CSA and were considered discrepant. Thirty-four causal mutations were detected, where of five had not previously been associated with assay discrepancy. These novel mutations were p.Tyr25Cys, p.Phe698Leu, p.Met699Leu, p.Ile1698Thr, and Ala2070Val. We found no difference between discrepant and nondiscrepant cases with either of the global assays.Conclusion There was a discrepancy between FVIII:C assays in almost half of the PwHA, which for some could lead to missed HA diagnoses or misclassification of severity. Genotyping confirmed that mutations associated with FVIII:C discrepancy cluster in the A domains of F8, and five mutations not previously associated with FVIII:C discrepancy was identified. Global hemostatic assays did not contribute to distinguish assay discrepancy in PwHA.
Keywords: clinical laboratory techniques; coagulation factor VIII; DNA mutational analysis; hemophilia A; diagnostic errors